Flood modeling of Naray-Khwar using HEC-RAS - Khan, Mujahid; Uzair, Aanis; Ali, Usama; Khan, Wisal (Journal of Himalayan Earth Sciences, 2020)
Flood Hazard Assessment of a river helps in predicting their behavior under different conditions. In this study, HEC-RAS model was used to simulate the steady flow water surface profile of Naray-Khwar, one of the largest water conveyance Khwar running through Peshawar carrying sewage affected significantly by urban interference. The methodology involved collection of geometry and flow data to perform various hydraulic calculations. For proper analysis, Naray-Khwar is divided into three channels with one junction under Nasir Bagh Bridge. Naray-Khwar Upper and Regi-Khwar Upper flow on the upstream while Naray- Khwar lower flows downstream of the junction. Horizontal distances along the corresponding elevations of 16 stations were measured using a total station. Due to the non-availability of measuring gauges, flow data was determined using rainfall data of Peshawar gauging station and was then converted into run-off using WinTR20 software. Frequency analysis was then carried out to calculate 2, 5, 10, 25, 50 and 100 years flood. The analysis showed that while most of the reaches at upstream of Nasir-Bagh Bridge are safe, it is the downstream side where the banks are over-topped by a very large margin.